Improvement of PVA-Glucomanan-Acrylamide Hydrogel as Base Material of Immobilization - Repita Sari; Sri Mulijani; Meri Suhartini (Syarif Hidayatullah State Islamic University, 2022)
Hydrogel products are currently widely used in various fields, one of which is agriculture. Most hydrogels are made of synthetic polymers because they have good absorption but are not biodegradable. Glucomannan is a natural polymer that is able to absorb large amounts of water and biodegradable but it is difficult to maintain water content. One method to improve the mechanical properties of hydrogels is by modifying the hydrogels through the formation of an interpenetrating network (IPN) between natural polymers and synthetic polymers. In this study, the IPN hydrogel based on polyvinyl alcohol and glucomannan and acrylamide as a crosslinker was made by combining freeze-thaw and gamma irradiation techniques. The results showed that the hydrogel water absorption after immersion for 24 hours was 311.09% where the weight of glucomannan was 1 g and acrylamide was 0.75 g and the irradiation dose was 30 kGy. The result of cumulative release test of paraquat immobilized into the hydrogel was 12.00% within 10 days. This indicates that the PVA-glucomannan-acrylamide hydrogel can be used as a controlled paraquat release matrix so as to minimize the effect on the overuse of pesticides.